Link-preserving interference-minimisation channel assignment in multi-radio wireless mesh networks. (2015) - Yen, Li-Hsing; Huang, Kuo-Wei
Using multiple channels with multiple radios per node in a wireless mesh network can potentially improve system capacity. This design requires the appropriate assignments of channels/radios to wireless backhaul links and creates a trade-off between conflicting constraints and requirements. This study attempts to maximise the number of operative links, where a link is operative if radios at both ends of the link share a common channel (i.e., are link-preserving) and experience sufficiently low co-channel interference. These two criteria are conflicting in nature. A link-centric, channel-first radio resource assignment scheme that considers physical interference model and tight radio constraint is proposed. The proposed approach ensures link preservation and assigns channels to links based on the predicted upper bound and lower bound of the accumulated co-channel interference associated with particular assignments. Simulation results indicate that the proposed algorithm outperforms existing approaches in the number of operative links, particularly when only a few channels, or many radios, are available.